Phenotypic Characterization of Chinese Rhesus Macaque Plasmablasts for Cloning Antigen-Specific Monoclonal Antibodies - Zhang, Fan; Wang, Longyu; Niu, Xuefeng; Li, Jiashun; Luo, Jia; Feng, Yupeng; Yang, Yanjia; He, Ping; Fan, Wenxia; Liang, Renshan; Zheng, Zhiqiang; Pan, Weiqi; et al. (Frontiers in Immunology, 2019)
Rhesus macaques (Macaca mulatta) are used as a human-relevant animal species for the evaluation of vaccines and as a source for cloning monoclonal antibodies (mAbs) that are highly similar to human-derived antibodies. Although antibody-secreting plasmablasts in humans are well defined and can be easily isolated for mAb cloning, it remains unclear whether the same phenotypic markers could be applied for isolating antibody-secreting plasmablasts from Chinese rhesus macaques. In this study, we evaluated a series of cell surface and intracellular markers and identified the phenotypic markers of plasmablasts in Chinese rhesus macaques as CD3–CD14–CD56–CD19–CD27–CD20–/lowCD80+HLA-DR+CD95+. After influenza virus vaccination, the plasmablasts in peripheral blood mononuclear cells (PBMCs) increased transiently, peaked at day 4–7 after booster vaccination and returned to nearly undetectable levels by day 14. Antigen-specific enzyme-linked immunosorbent spot (ELISPOT) assays confirmed that the majority of the plasmablasts could produce influenza virus-specific antibodies. These plasmablasts showed transcriptional characteristics similar to those of human plasmablasts. Using single-cell PCR for immunoglobulin heavy and light chains, most mAbs cloned from the CD3–CD14–CD56–CD19–CD27–CD20–/lowCD80+HLA-DR+CD95+ plasmablasts after vaccination exhibited specific binding to influenza virus. This study defined the phenotypic markers for isolating antibody-secreting plasmablasts from Chinese rhesus macaques, which has implications for efficient cloning of mAbs and for the evaluation of plasmablast response after vaccination or infection in Chinese rhesus macaques.